The effectiveness of the zakāt community development program in improving the people’s economy - Syarifah, Lailatus; Abdullah, Irwan; Elizabeth, Misbah Zulfa (Journal of Islamic Economics Management and Business (JIEMB), 2022)
Zakāt is not just giving some money or basic food to support mustaḥiq within a few days or a few weeks, but how mustaḥiq can fulfil his needs with the capabilities he has. To be precise, this research examines the effectiveness of the zakāt community development program in Jungsemi Village, Kendal Regency. This program’s main funds come from zakāt, which Baznas of Kendal Regency manages. The main objective of this program is to empower local communities, which are expected to improve people’s welfare, especially productive zakāt mustaḥiq; so that they can transform into muzakkī. This program has existed since 2020. The methods of this research used qualitative research. The data collection used are interviews, observation, and documentation. The results of this study show the effectiveness of the zakāt community development program in improving the people’s economy. Here the focus is on productive zakāt mustaḥiq in the community development zakāt program in Jungsemi, Kendal Regency.